Peptide Nucleic Acids Methods and Protocols - Nielsen, Peter E.; Nielsen, Peter E. (Methods in Molecular Biology,, 2002)
Peptide nucleic acid (PNA) technology continues to grow in importance throughout molecular biology, genetic diagnostics, and molecular medicine. In Peptide Nucleic Acids: Methods and Protocols, Peter Eigil Nielsen has assembled a critically evaluated collection of PNA protocols that are either already well established around the world, such as PCR-clamping and in situ hybridization, or that display promise of significant future impact. Basic methods for PNA oligomer synthesis and analysis have also been included. Written by experts with hands-on experience in the methods they describe, these readily reproducible protocols contain detailed step-by-step instructions, tips on avoiding pitfalls and on extending the method to other situations, and introductory material explaining the theory behind the process. Up-to-date and highly practical, Peptide Nucleic Acids: Methods and Protocols provides for both novice and experienced researchers a thorough and easy introduction to the optimal use of today's PNA technology across a wide variety of fields, including molecular biology, medicinal chemistry, genetic diagnostics, and drug development.